2015
DOI: 10.1158/1535-7163.mct-15-0419
|View full text |Cite
|
Sign up to set email alerts
|

R-Ketorolac Targets Cdc42 and Rac1 and Alters Ovarian Cancer Cell Behaviors Critical for Invasion and Metastasis

Abstract: Cdc42 (cell division control protein 42) and Rac1 (Ras-related C3 botulinum toxin substrate 1) are attractive therapeutic targets in ovarian cancer based on established importance in tumor cell migration, adhesion and invasion. Despite a predicted benefit, targeting GTPases has not yet been translated to clinical practice. We previously established that Cdc42 and constitutively active Rac1b are overexpressed in primary ovarian tumor tissues. Through high throughput screening and computational shape homology ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 48 publications
2
88
0
Order By: Relevance
“…Interferon regulatory factor 4 binding protein activates Rac1, RhoA, and Cdc42 to regulate EMT and motility in breast cancer cells [31]. It has been shown that Cdc42 serve as an oncogene in various tumors such as breast cancer, colorectal cancer, and ovarian cancer [32-34]. These findings suggest that Cdc42 plays an oncogenic role in cancers by influencing cell metastasis and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon regulatory factor 4 binding protein activates Rac1, RhoA, and Cdc42 to regulate EMT and motility in breast cancer cells [31]. It has been shown that Cdc42 serve as an oncogene in various tumors such as breast cancer, colorectal cancer, and ovarian cancer [32-34]. These findings suggest that Cdc42 plays an oncogenic role in cancers by influencing cell metastasis and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously (7,8), racemic 15K has at least two direct targets: (i) R-form directly inhibits the GTPase RAC that activates PAK1, and (ii) S-from directly inhibits COX-2 whose expression depends on PAK1. Our present test concerning the effect of 15K on C. elegans is basically same as phenotypes of PAK1 KO (5) as well as effect of natural PAK1-blockers such as propolis and triptolide (13,14), confirming that the down-regulation of both PAK1 and COX-2 by 15K leads to a significant extension, instead of shortening, of its lifespan.…”
Section: K Extends the Health Lifespan Of C Elegansmentioning
confidence: 86%
“…15K is a highly cell-permeable 1,2,3-triazolyl ester of ketorolac (Figure 1), a racemic COOH-bearing PAK1-blocker/COX-2 inhibitor, which down-regulates PAK1 in R-form, as well as directly inhibits COX-2 in S-form (7,8). 15K is over 500-5,000 times more potent than ketorolac to inhibit the growth of cancer cells such as A549 (lung) and B16F10 (melanoma) cell lines with IC 50 ranging 5-24 nM (7).…”
Section: Introductionmentioning
confidence: 99%
“…50,51 We showed that cells expressing VAV1-GSS were exquisitely sensitive to azathioprine, which inhibits activation of RAC1 but not of CDC42 or RHOA, 33,34 Other clinically available drugs that inhibit RAC1 and have been proposed to be repurposed as anticancer agents include metformin, statins such as simvastatin, and R-ketorolac. [52][53][54] RAC1 small molecule inhibitors are in ongoing development. 55,56 Taken together, these data suggest RAC1 inhibition is a potential therapeutic strategy for PTCLs with VAV1 fusions, noting, however, that these fusions are present in the minority of PTCLs.…”
Section: Discussionmentioning
confidence: 99%